2004
DOI: 10.1159/000080130
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pantoprazole versus Ranitidine in the Treatment of Patients with Symptomatic Gastroesophageal Reflux Disease

Abstract: Background/Aim: Gastroesophageal reflux disease (GERD) is a prevalent disease associated with a high symptom burden and a reduced quality of life. This multicenter, randomized, double-blind study compared relief from key GERD symptoms (heartburn, acid eructation, and pain on swallowing) and from other gastrointestinal symptoms (epigastric pain, vomiting, nausea, flatulence, retching, and retrosternal feeling of tightness) and safety profiles of the proton pump inhibitor pantoprazole and the H2 antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…Ademais, em relação à segurança da droga, vários efeitos adversos, como infecção do trato respiratório superior, vômito, diarréia, pneumonia, lesão cutânea, fadiga e tremor foram observados. Por outro lado, estudos em adultos comprovaram a superioridade dos IBP sobre os IH2 na cicatrização de esofagite grave 30,31 . Séries de casos com essa classe de drogas em crianças têm selecionado pacientes a partir da falha terapêutica com IH2, alcançando grandes taxas de alívio de sintomas e cicatrização de mucosa esofágica [32][33][34][35] .…”
Section: Esofagite Erosivaunclassified
See 1 more Smart Citation
“…Ademais, em relação à segurança da droga, vários efeitos adversos, como infecção do trato respiratório superior, vômito, diarréia, pneumonia, lesão cutânea, fadiga e tremor foram observados. Por outro lado, estudos em adultos comprovaram a superioridade dos IBP sobre os IH2 na cicatrização de esofagite grave 30,31 . Séries de casos com essa classe de drogas em crianças têm selecionado pacientes a partir da falha terapêutica com IH2, alcançando grandes taxas de alívio de sintomas e cicatrização de mucosa esofágica [32][33][34][35] .…”
Section: Esofagite Erosivaunclassified
“…A terapia de inibição ácida com IBP é capaz de impedir a evolução da estenose e de reduzir a necessidade de dilatações endoscópicas 2,31 .…”
Section: Estenose Péptica E Esôfago De Barrettunclassified
“…Although more effective than other current commercially available treatment methods, the use of PPIs can result in a number of known rare side effects, including nausea, diarrhea, headache, insomnia, and anaphylaxis. [27,31,32] The first-generation PPIs that are currently used have also shown significant interpatient variability and in many cases may adversely interact with other drugs. [16] Cholecystokinin 2 receptor antagonists The CCK 2 receptor antagonists ( Figure 6) are a new class of drugs designed to block the CCK 2 receptors, thereby inhibiting gastric acid secretion.…”
Section: Histamine H 2 -Receptor Antagonistsmentioning
confidence: 99%
“…On the other hand, studies on adults have confirmed the superiority of PPI over H2RA for healing severe esophagitis. 30,31 Studies with this class of drugs in children have primarily selected patients based on treatment failure with H2RA, achieving high rates of symptom relief and esophageal mucosa healing. [32][33][34][35] Cucchiara et al compared both drugs in children.…”
Section: The Young Child With Abdominal Painmentioning
confidence: 99%